REMODELING OF THE HEART AND VESSELS IN ATRIAL FIBRILLATION PATIENTS WITH CHRONIC HEART FAILURE ACCORDING TO CYSTATIN C-RELATED GLOMERULAR FILTRATION RATE - S. V. Mironova; E. A. Polyanskaya; M. V. Surovtseva (Российский кардиологический журнал, 2018)
Aim. To investigate on structural and functional specifics of the left cardiac chambers and arteries in patients with permanent atrial fibrillation (AF) comorbid with chronic heart failure (CHF) of ischemic origin, with relation to cystatin C-dependent glomerular filtration rate (GFR).Material  and  methods. Sixty patients, age 35-60 y. o., with permanent AF of ischemic origin. All patients underwent echocardiography for the dysfunction verification: systolic function was assessed by ejection fraction of the left ventricle by Simpson, diastolic function was assessed via the velocity of transmitral currents and visualization of tissues of the mitral valve; Holter ECG monitoring was done, as volumetric sphygmopletysmography of peripheral arteries, assessment of kidney function by Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) by creatinine and cystatin C, evaluation of the status of collagen production by the tissue inhibitor of matrix metalloproteases type 1 (TIMP-1), measurement of NT-proBNP. In the first part of the study, patients were selected to 3 groups: by GFR <30 mL/min/1,73 m2, 30-60 mL/min/1,73 m2 and >60 mL/min/1,73 m2. In the second — by cystatin C levels below or higher than the referent.Results. In the permanent AF with ischemic CHF patients, concentration of cystatin C in the blood correlates strongly depending on the NT-proBNP (r=0,60; р=0,003), left ventricle myocardial mass index (r=0,68; р=0,005), mean E/e’ (r=0,73; p<0,001), isovolumetric relaxation time (r=0,53; р=0,012), mean daily heart rate (r=0,51; р=0,016); correlates weakly with TIMP-1 (r=0,26, p=0,002); correlates negatively strongly with SDNN (r=-0,59; р<0,001). The GFR (CKD-EPIcys) correlates negatively strongly with the septal e’ (r=-0,51; р=0,041), with R-AI (r=-0,74; p<0,001), with CAVI1 (r=-0,53; р=0,008), and directly moderately with SDNN (r=0,42; р<0,001).Conclusion. Assessment of cystatin C in the blood and cystatin C-dependent GFR in permanent AF and ischemic CHF are not only the early markers of CKD, but are the risk factors of development and progression of target organs (heart, vessels).